Hybrid Powerplant Using Solar and Wind Energy - Tri Widyaningrum Vivi; Sahru Romadhon Ahmad (MATEC Web of Conferences, 2022)
Solar and wind energy sources can be used sustainably without worrying about running out. However, both energy sources have a weakness, namely in the rainy or cloudy season the energy produced is not large. So that an alternative is sought, namely by combining them which is usually called a hybrid system. The purpose of developing hybrid technology here is that if one energy source cannot produce energy, the other energy source will replace it as an energy supplier to the load. In the hybrid system, the utilization of solar energy uses a solar cell, while for the utilization of wind energy it uses a turbine generator.From the results of the study, it can be seen that the electrical energy produced by solar power plants is much greater than the electrical energy produced by wind power plants. In addition, solar power plants are still able to produce electrical energy, even though the solar cell is not exposed to sunlight. Meanwhile, in wind power plants, the electrical energy produced depends on the speed of the wind that blows. This means that for areas where the wind speed is unstable, it is better to use solar power plants compared to wind power plants.